CENTROID-MOMENT TENSOR SOLUTIONS FOR APRIL-JUNE, 1983 - Dziewonski, A; Franzen, J; Woodhouse, J (1983)
Centroid-moment tensor solutions are presented for 99 earthquakes that occurred during the second quarter of 1983. © 1983.